2016
DOI: 10.7717/peerj.2689
|View full text |Cite
|
Sign up to set email alerts
|

The origin of the lower fourth molar in canids, inferred by individual variation

Abstract: BackgroundAn increase in tooth number is an exception during mammalian evolution. The acquisition of the lower fourth molar in the bat-eared fox (Otocyon megalotis, Canidae, Carnivora, Mammalia) is one example; however, its developmental origin is not clear. In some canids (Canidae), individual variation exist as supernumerary molar M4. This study focuses on the acquisition of the lower fourth molar in canids and proposes that the inhibitory cascade model can explain its origin.MethodsOcclusal view projected a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 26 publications
0
3
0
2
Order By: Relevance
“…Más recientemente, Asahara (2013aAsahara ( , 2013bAsahara ( , 2014aAsahara ( , 2014bAsahara ( , 2016 estudió la variación cranial y dentaria en Nyctereutes procyonoides y otros cánidos, cuantificando la presencia de molares extra (m4) en relación al tamaño relativo de los otros molares inferiores (m2/m1, m3/m1), así como el tamaño del m1. En un primer análisis utilizó morfometría geométrica para explorar la variación del cráneo entre ocho poblaciones (y un total de 177 especímenes) distribuidas a lo largo de Japón (Asahara, 2013a).…”
Section: Resultados Variación Intraespecífica De Caracteres Craneoden...unclassified
See 1 more Smart Citation
“…Más recientemente, Asahara (2013aAsahara ( , 2013bAsahara ( , 2014aAsahara ( , 2014bAsahara ( , 2016 estudió la variación cranial y dentaria en Nyctereutes procyonoides y otros cánidos, cuantificando la presencia de molares extra (m4) en relación al tamaño relativo de los otros molares inferiores (m2/m1, m3/m1), así como el tamaño del m1. En un primer análisis utilizó morfometría geométrica para explorar la variación del cráneo entre ocho poblaciones (y un total de 177 especímenes) distribuidas a lo largo de Japón (Asahara, 2013a).…”
Section: Resultados Variación Intraespecífica De Caracteres Craneoden...unclassified
“…Según este autor la variación observada dentro de las poblaciones sería neutral, pero las diferencias observadas con respecto a la población de Hokkaido (la cual sería otra subespecie), que básicamente involucran cambios en el tamaño relativo del parietal, el frontal y de la posición del arco cigomático, estarían relacionadas con factores climáticos. En un trabajo posterior (Asahara, 2016) Son escasos los estudios realizados con buenas muestras de cánidos de América del Sur y, en general, corresponden a estudios morfométricos enfocados a resolver problemas sistemáticos y de variación geográfica, en los cuales la cuantificación de la variación morfológica no es el principal objetivo. Por ejemplo, estudios basados en morfometría tradicional y geométrica (Zunino et al, 1995; encontraron que Lycalopex griseus y Lycalopex gymnocercus forman una variación clinal en la que los especímenes disminuyen de tamaño hacia el sur y el oeste en respuesta a cambios ambientales (mayor aridez).…”
Section: Resultados Variación Intraespecífica De Caracteres Craneoden...unclassified
“…In a similar study of 82 skulls, hyperdontia was identified in 6 skulls [19,24]. Asahara (2016) [25], who found that in 153 studied skulls of raccoon dogs, M 4 extra tooth accounted for 2.61% of the pathologies, also gives a plausible explanation of the causes of hyperdontia. It is mainly associated with the high content of insects in the diet.…”
Section: Discussionmentioning
confidence: 92%
“…These differences are often triggered by geographic isolation and speciation, such as observed in the Persian mole ( Talpa davidiana ; Kryštufek et al, 2001 ) and Japanese mole ( Mogera wogura ; Asahara et al, 2012 ). Nevertheless, an increased number of molars is an extremely rare event observed in only a few taxa, such as the bat-eared fox ( Otocyon megalotis ), and can be impacted by the evolution of different feeding behaviors and explained using an inhibitory cascade model ( Asahara, 2013 ; Asahara, 2016 ; Asahara et al, 2016 ). For example, adaptation toward an increased bite force in the hypercarnivorous bush dog ( Speothos venaticus ) resulted in an enlarged M 1 , thus prohibiting the development of M 3 dentition ( Damasceno et al, 2013 ).…”
Section: Discussionmentioning
confidence: 99%
“…If the inhibitory cascade model is valid in Erinaceidae, the presence of a supernumerary M 4 in Mesechinus wangi sp. nov. could be attributed to a combination of genetic bottleneck and isolation (hypothetically after long-distance dispersal from northern China) as well as adaptive selection from an omnivorous-insectivorous diet toward a highly omnivorous one resulting in reduced inhibition during the development of the upper molars ( Asahara, 2016 ; Asahara et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%